2005
DOI: 10.1007/s10162-005-0004-9
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effects of Exposing DBA/2J Mice to an Augmented Acoustic Environment on Histological Changes in the Cochlea and Anteroventral Cochlear Nucleus

Abstract: DBA/2J (D2) mice, which exhibit very early progressive sensorineural hearing loss, were treated nightly with an augmented acoustic environment (AAE) initiated before the onset of hearing, and consisting of repetitive bursts of a 70-dB sound pressure level (SPL), 4Y25 kHz noise band. At 55 days of age, AAEtreated mice exhibited less elevation of auditory brainstem response thresholds, fewer missing hair cells, and greatly reduced loss of anteroventral cochlear nucleus (AVCN) volume and neuron number compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 35 publications
7
45
1
Order By: Relevance
“…Application of AAE in auditory research has a long history and was first employed in mice with genetic agerelated sensorineural hearing loss (Turner and Willott, 1998;Willott and Turner, 1999). A series of studies suggested that AAE can ameliorate the severity and time course of hearing loss as well as OHC loss in C57BL/6J and DBA/2J mice (Turner and Willott, 1998;Willott and Turner, 1999;Willott and Bross, 2004;Willott et al, 2001Willott et al, , 2005Willott et al, , 2006aWillott et al, ,b, 2008). …”
Section: Introductionmentioning
confidence: 92%
“…Application of AAE in auditory research has a long history and was first employed in mice with genetic agerelated sensorineural hearing loss (Turner and Willott, 1998;Willott and Turner, 1999). A series of studies suggested that AAE can ameliorate the severity and time course of hearing loss as well as OHC loss in C57BL/6J and DBA/2J mice (Turner and Willott, 1998;Willott and Turner, 1999;Willott and Bross, 2004;Willott et al, 2001Willott et al, , 2005Willott et al, , 2006aWillott et al, ,b, 2008). …”
Section: Introductionmentioning
confidence: 92%
“…(i.e., approximately 160μm and 320μm posterior to the rostral pole, respectively). Measurements were made on these two standard frontal sections of each mouse, as in our previous studies (Willott and Bross, 2004;Willott et al, 2005). These sections lie, respectively, within the anterior and posterior divisions of the AVCN in the atlas of Trettel and Morest (2001), where additional cytoarchitectonic details may be found.…”
Section: Analysis Of Avcn Sectionsmentioning
confidence: 99%
“…First, treatment with a middle-frequency (MAAE, peak SPL from 8-20 kHz) had ameliorative effects on progressive hearing loss in B6 and other inbred strains (Turner and Willott, 1998;Willott an Turner, 1999;Willott and Bross, 2004;Willott et al, 2001;2005;2006a,b). Vazquez et al (2004) also found evidence of OHC preservation after moderate noise exposure.…”
Section: Previous Aae Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, structural improvements induced by the AAE were uncovered in DBAs, including preservation of hair cells and AVCN neurons, and reduction of AVCN volume declines with age (Willott et al 2005 ). Turner and colleagues ( 2013 ) also exposed old (22-23 months) CBA mice to AAEs for 6 weeks, and found structural and functional benefi ts for males, but not females, suggesting infl uences of hormonal differential effects late in life.…”
Section: Altering the Time Course Of Arhl In Mouse Strains: Interventmentioning
confidence: 96%